In Search of Ambidextrous Professors - Markides, Costas (Academy of Management Journal, 2007)
An examination of the growing knowledge gap that exists between scholars who produce academic research geared towards business management and the individuals who work in the field of business management. The two main problems that exist are scholars not producing relevant research and practitioners who are not receiving the research that is relevant. The author discusses some of the proposed solutions to close this gap and examines why this gap has been able to persist.